2015
DOI: 10.3343/alm.2015.35.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of the TGFBI Gene in Consecutive Korean Patients With Corneal Dystrophies

Abstract: BackgroundMutations in the transforming growth factor β-induced gene (TGFBI) are major causes of genetic corneal dystrophies (CDs), which can be grouped into TGFBI CDs. Although a few studies have reported the clinical and genetic features of Korean patients with TGFBI CD, no data are available regarding the frequency and spectrum of TGFBI mutations in a consecutive series of Korean patients with clinically diagnosed CDs.MethodsPatients with any type of CD, who underwent both ophthalmologic examination and TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
1
23
1
1
Order By: Relevance
“…Among epithelial–stromal TGFBI dystrophies, GCD2 was the most prevalent type (53%), followed by LCD (39%) and TBCD (8%). The prevalence of GCD2 among TGFBI ‐associated dystrophies was lower in this study than previously reported prevalences of 94.8% and 89.9% in Korean patients. Our study had more genetically confirmed LCD and TBCD patients included than previous reports.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Among epithelial–stromal TGFBI dystrophies, GCD2 was the most prevalent type (53%), followed by LCD (39%) and TBCD (8%). The prevalence of GCD2 among TGFBI ‐associated dystrophies was lower in this study than previously reported prevalences of 94.8% and 89.9% in Korean patients. Our study had more genetically confirmed LCD and TBCD patients included than previous reports.…”
Section: Discussioncontrasting
confidence: 91%
“…Case reports of a single type of corneal dystrophy and a few genetic studies of TGFBI ‐related corneal dystrophies in Korean patients have been published . But, a comprehensive genotyping study encompassing an array of genes associated with different types of corneal dystrophies in Korean patients as well as in Asian patients has not been carried out.…”
mentioning
confidence: 99%
“…TGFBI gene mutations are primarily involved in autosomal dominant inherited CDs characterized by the progressive accumulation of extracellular insoluble protein deposits within corneal tissue, which can present as amyloid, nonamyloid (granular), or both [15, 16]. Depending upon deposition features and locations in the corneal layers, disease-causing mutations identified in the TGFBI gene have been involved in various phenotypes, including Thiel–Behnke corneal dystrophy (TBCD, OMIM 602082), Reis–Bucklers corneal dystrophy (RBCD, OMIM 608470), Groenouw type I granular cornea dystrophy (CDGG1, also known as GCD1, OMIM 121900), Avellino corneal dystrophy (ACD, OMIM 607541), lattice corneal dystrophy types I and IIIA (LCD1, OMIM 122200 and LCD3A, OMIM 608471), and epithelial basement membrane corneal dystrophy (EBMD, OMIM 121820) [2, 4, 17]. Currently, TGFBI -CDs present as dominantly inherited monogenic forms with a high penetrance of 60–90% [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several phenotypes have been described according to corneal layer alterations and the investigation of pathogenic mutations in the TGFBI gene, with the exception of metabolic effects. Pathogenic mutations in the TGFBI gene have been implicated in various phenotypes depending on the degree of damage to the corneal layer, such as Thiel-Behnke corneal dystrophy (TBCD, OMIM 602082), Reis-Bucklers corneal dystrophy (RBCD, OMIM 608470), Groenouw granular corneal dystrophy type I (CDGG1), lattice corneal dystrophy I and IIIA (LCD1, OMIM 122200 and LCD3A, OMIM 608471) and corneal dystrophy with epithelial basement membrane (EBMD, OMIM 121820) (15,16). Such dystrophy is called variant LCD by IC3D conventions (5).…”
Section: Introductionmentioning
confidence: 99%